A RESISTÊNCIA À INSULINA COMO FATOR DE DISTÚRBIOS METABÓLICOS EM CRIANÇAS E ADOLESCENTES OBESOS DE GUARAPUAVA, PARANÁ - Lemos, Leandro Coelho (2016)
Introduction: There is great interest in recognizing predictors of diseases or disorders in childhood. Especially when it comes to issues such as obesity, which when achieved in childhood, it is difficult to convert into adulthood. Excess visceral adiposity in adults is associated with metabolic abnormalities, but when it comes to children and / or adolescents the results are conflicting. Obesity, RI, dyslipidemia and hypertension have strong association, both in childhood and in adulthood. Objectives: To assess the effects of insulin resistance in metabolic disorders and obesity indicators in children and adolescents overweight. Methods: This study is a cross-sectional ex-post-facto. It was held at the Universidade Estadual do Centro Oeste Campus CEDETEG, Guarapuava Paraná, between the years 2012 and 2013. It is part of the Childhood Obesity Control and Treatment Project. Through their parents / guardians, they conducted enrollment in the voluntary project, the total of 120 children and adolescents. The participants attended a clinical laboratory for blood collection fasting for determination of glucose, insulin and lipid profile (HDL-C, LDL-C, TG and TC). From the glucose and insulin was calculated IR index by HOMA-IR method Body Mass Index (BMI = weight kg / height m²) was used for the classification of nutritional status. For the BMI cutoff points the WHO z-score standards were used. For the classification of DC measurements were used to Mccarthy recommendations, Jarrett & Crawley (2001). The percentage of fat (% BF) was estimated by electrical bioimpedance. He used the Shapiro-Wilk test, the Mann-Whitney U test and ANCOVA. For the assumption of homogeneity of variances checked by Levene's test. Following Pearson correlation analysis was applied and after the Logistic Regression Binary was employed. Finally, survival analysis using the Kaplan Mayer test. Results: Among resistant and non-resistant to insulin, after correction for age, we found significant differences for MC, BMI, GC, CC, LDL, TG, IR, HOMA. For TC, LDL and TG was observed significant differences in the proportions of resistant and non-resistant to insulin. The finding of the downward curve RI survival from TG confirms the trend that there is influence of changes in TG in RI and the higher the TG rate, the greater the chances that individual be resistant to insulin.